Becoming queer, being African: re-thinking an African queer epistemological framework - Ombagi, Eddie Cavines (My University, 2019)
This project was initiated by the need to read queer lives and subjectivities in Kenya in the face of the hostile and violent homophobic religious and nationalistic rhetoric. In this project, I argue that Kenya has become a site of and frame for the contradictions of queer liveability on one hand and queer fungibility on the other. What I mean is despite virulent attacks by the political and religious section of the country against queer sexual expressions, intimacies and visibility, there exists a productive queer existence that is predicated on both embodied lived experiences and spatial subjectivity. In this project, I investigate the selected spaces – both geographical and literary - in ways that enable its users to perform this visibility and allow for the myriad possibilities that exist within this contradiction. I speculate on how the users imagine themselves within these spaces and the kinds of significations and meanings that accrue to the users subjectivities. I further contend that the structure of these spaces allows for queer, queering and queered flows that makes it possible for queer users to subvert them in ways that enables them to read, locate and recognize queer subjectivities. My critique is about how we understand queer subjectivities, lives and bodies outside of the common narratives of decadence, violence and its theorization as a western import. I wonder what sorts of positionalities and intensities accrue when Nairobi queer bodies inhabit spaces as they variously transition. Here, I aim to show that reading and contextualizing these connected and disconnected liminal spaces, reveals a deeper understanding of how queer individuals restructure the spaces that they occupy in order to account for, and narrativise their lives in light of the socio-political conditions in Kenya. My reading draws on insights on ‘becoming’ to insist that to adequately and forcefully locate queer bodies, expressions, desires and spaces within popular imaginaries and cultures, a theoretical spectrum that calls attention to the incoherence and unintelligibility of sexualities in nuanced complexities around community and/or the social fabric as well as lived experiences, spatial subjectivities, and embodied existences is necessary.
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy. January, 2019
Keywords: Gender identity; Queer theory; Ethnology--Africa